Efficacy of HIVEC in patients with high-risk non-muscle invasive bladder cancer who are contraindicated to BCG and in patients who fail BCG therapy. (1st January 2021) - Doisy, Laure; Cimier, Arnaud; Adypagavane, Aurélien; Walz, Jochen; Marquette, Thibault; Maubon, Thomas; Rybikowski, Stanislas; Fakhfakh, Sami; Loverde, Kevin; Mottet, Nicolas; Irani, Jacques; Lechevallier, Eric; et al.
Abstract: Purpose: To evaluate Hyperthermic-Intra-Vesical Chemotherapy (HIVEC) efficacy regarding 1-year disease-free survival (RFS) rate and bladder preservation rate in patients with High-risk Non-Muscle Invasive Bladder Cancer (NMIBC) who fail BCG therapy or are contraindicated to BCG. Methods: Between June 2016 and October 2019, patients treated with HIVEC for mostly high-risk NMIBC who failed BCG or BCG-naive if BCG contraindicated have been included in our study. These patients had a theoretical indication for cystectomy but were ineligible for surgery or refused it. Results: Fifty-three patients, median age 72 [39–93] years, were included in this study ( n = 29 BCG-failure and n = 24 BCG-naive). The median follow-up was 18 months. The bladder preservation rate was 92.4%. The 12 months-RFS rate was 60.5%. The RFS rates for BCG-naive and BCG-failure groups were respectively 70% and 52.2% at 12 months. Three patients progressed to muscle infiltration, all in the BCG-failure group and all in the very high-risk EORTC group. Two of them developed metastatic disease and died from bladder cancer. Conclusion: Chemohyperthermia using HIVEC achieved a RFS rate of 60% at 1 year and enabled a bladder preservation rate of 92%. Given the low risk of progression in the BCG-naive group, HIVEC could be a good alternative. Conversely, for patients with very high-risk tumors that fail BCG, cystectomy should remain the standard of care and HIVEC may be discussed cautiously for patients who are not eligible for surgery and well informed of the risk of progression to muscle-invasive disease.